Didactics of writing using Information and Communication Technologies: teaching reflections - Rosa- Coronado , Maria (2022)
This article is born from the doctoral research: Teaching beliefs about the teaching of writing from the use of ICT in basic secondary education in the urban area of the District of Turbo, Antioquia, whose protagonist are the teachers of the Spanish language area of basic secondary education belonging to decree 2277 and 1278 named in property. Teaching beliefs directly influence the teaching-learning processes of all areas of knowledge; it could be said that in these are all the answers to all the questions and unknowns that revolve around the improvement of education, the inclusion of ICT and the development of competences, skills and abilities of thought and science and technology itself. The scriptural process frames great relevance in interpreting, analyzing, disseminating and transforming knowledge in industry 4.0; develop critical thinking; breaking with traditional paradigms, training competent, humanistic and highly technological students are challenges and challenges that the teacher must face day by day, month by month, year by year therefore it is necessary to understand how the beliefs that teachers have are configured and what is the professional and theoretical domain that they use in their pedagogical practices to renew curricula,  transform careers and use in an assertive and ideal way the educational resources offered by the internet through platforms, social networks among others that help improve higher-order thinking skills; in this document a theoretical and reflective journey is made that will allow the reader to confront hidden realities within the same educational system and at the same time find clues to carry out future and interesting research in the field of education with the aim of unveiling strategies that allow achieving the ideal of man that you want to form in society 4.0.